2014
DOI: 10.1007/s12035-014-8931-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Motor Neuron-Like Cell Differentiation of hEnSCs on Biodegradable PLGA Nanofiber Scaffolds

Abstract: Human endometrium is a high-dynamic tissue that contains human endometrial stem cells (hEnSCs) which can be differentiated into a number of cell lineages. The differentiation of hEnSCs into many cell lineages such as osteoblast, adipocyte, and neural cells has been investigated previously. However, the differentiation of these stem cells into motor neuron-like cells has not been investigated yet. Different biochemical and topographical cues can affect the differentiation of stem cells into a specific cell. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 45 publications
2
38
0
Order By: Relevance
“…Our results showed that the differentiation potential of EnSCs into motor neuron-like cells on poly(lactic-co-glycolic acid) (PLGA) electrospun nanofibrous scaffolds better than those cultured in the culture plates [37].…”
Section: Discussionmentioning
confidence: 80%
“…Our results showed that the differentiation potential of EnSCs into motor neuron-like cells on poly(lactic-co-glycolic acid) (PLGA) electrospun nanofibrous scaffolds better than those cultured in the culture plates [37].…”
Section: Discussionmentioning
confidence: 80%
“…Consequently, our results showed that collagen-coated PCL nanofibers could provide better condition for differentiation of WJMSCs to motor neurons. The results of our study open new opportunities for further investigations on the modification of nanofibrous scaffolds, and moreover, the combination of stem cells and nanomaterial expected to be an important tool in treating neural diseases such as spinal cord injury [62][63][64].…”
Section: Evaluation Of Wjmscs Differentiation Into Motor Neuron-like mentioning
confidence: 82%
“…Alignment of polymer backbone structures along fiber axes forms crystal domains [150][151][152], which have provided a foundation for optoelectronics such as nanofiber light sources with color tunability and waveguide capabilities and nanofiber lasers [39,146,148,. Biologically, hybrid nanofiber scaffolds have provided a cell niche conducive to improved attachment, proliferation, and cell differentiation [190][191][192][193][194][195][196][197][198], as well as targeted drug delivery carriers [198][199][200][201][202][203][204][205][206]. Filtration using ONFs [207] equipped with activated carbon has revealed adsorption of volatile organic compounds (VOCs) present in the air [208][209][210], and Scholten et al reported that adsorption and desorption of VOC by electrospun nanofibrous membranes (ENMs) were faster than that of conventional activated carbon [208].…”
Section: Organic Micro-and Nano-fiber Systemsmentioning
confidence: 99%